Body dissatisfaction, muscle dysmorphia and attitudes towards doping in exercise practitioners: a study regarding gender, educational level and age group - Costa, Nathan Leonardo Gomes; Sousa, Mariana Rílary Silvestre; Freire, Gabriel Lucas de Morais; Oliveira, Daniel Vicentini de; Fidelix, Yara Lucy; Moraes, José Fernando Vila Nova de; Nascimento Junior, José Roberto Andrade do (Acta Scientiarum. Health Sciences, 2025)
Body dissatisfaction (BD) is a conception constructed from influences since childhood, with the practice of exercise being an alternative to obtain the ideal body. Muscle dysmorphia (MD) is characterized as an exaggerated visualization of body imperfections and can lead to the search for substances such as anabolic steroids (AAS). Therefore, the aim of the present study was to compare body image (BI), MD and attitudes towards doping according to gender, educational level and age group of exercise practitioners at gyms. A total of 264 individuals (92 men and 172 women), with a mean age of 27.43 years (SD = 7.03), participated in the study. The instruments used were the Body Shape Questionnaire (BSQ), the Questionnaire of Attitudes towards Doping in Fitness (QAD-fit) and the Adonis Complex questionnaire (ACQ). Data analysis was conducted using the Kolmogorov-Smirnov, independent Student’s t-tests and MANOVA (p<0.05). The results showed a higher BD among women, and more behaviors towards doping in the males (p<0.05). A positive relationship was found between attitudes towards doping in individuals who had completed high school. Also, higher scores for attitudes and beliefs towards doping in the age group of 31-40 years was found. It is concluded that sociodemographic factors such as gender, age group and educational level maybe involved in BD, MD and in behaviors towards doping in people who practice exercise at gyms.